The causes of differences opinions among jurists - Azran, Muhammad Irfan Imaduddin; Ramli, Muhammad Adi Irfan; Sallehudin, Sadiq Najwan; Zuhairi, Muhammad Amir Iqbal; Hamzah, Amirul Khalis (2022)
This article aims to explain the concept of ikhtilaf and the three main factors that cause the occurrence of ikhtilaf among the Companion jurists in ijtihad. In presenting some examples of differences among the jurists of the Sahabah ra, the views of the tabi'in jurists and the mazhab imams were also stated at the end of some of the issues discussed. The objective of this article is to prove that the occurrence of ikhtilaf among mujtahidin jurists in ijtihad is caused by factors that are deliberately provided by the syar'a coinciding with the essence of Islamic shari'a which is rabbinical, comprehensive, flexible, realistic, and eternal.